Investigation of Punicic Acid Effects on Matrix Metalloproteinase Genes Expression in Bovine Fibroblast like-Synoviocytes as a Model of Osteoarthritis - Taherian; H Maghsoudi; A Vaziri; M Alebouyeh (Institue of Medicinal Plants, ACECR, 2018)
Background: Osteoarthritis (OA) is a progressive, age-associated disease that is characterized with cartilage destruction, subchondral bone remodeling and inflammation of the synovial membrane. Considering the complications of common treatments of OA, including non-steroidal anti-inflammatory drug (NSAIDs) and corticosteroids, investigating new treatments for this disorder is crucial. Recently, the role of matrix metalloproteinases (MMPs) expression in pathogenesis of OA has attracted attention. Objective: This study aimed to explore the effect of punicic acid (PA) in inhibition of MMPs gene expression in LPS-stimulated Bovine Fibroblast-like synoviocytes (BFLS) as a model of OA. Methods: In the first stage, the toxicity of PA was measured using MTT assay on BFLS cells. Afterward, the cells were stimulated by LPS (Lipopolysaccharide) and MMPs (Matrix Metalloproteinase) expression level in the BFLS cells were investigated using Real-Time PCR, in vitro Migration and Gelatin Zymography, Western Blot Analysis, ELISA Assay and Invasion Assay. Results: The results showed that PA significantly decreased MMP-9 expression levels in LPS-stimulated BFLS cells; also, it suppressed migration and invasion of the mentioned cells. However, PA had no significant effect on MMP-1-2-3. Conclusion: Based on our results PA could significantly reduce the activity and inflammatory effect of MMP-9 in OA, its potential role as a supplementary agent to common NSAIDs and corticosteroids was confirmed. Nonetheless, cellular modeling does not significantly confirm the beneficial effect of OA in patients.